Lightweight hydraulic power transmission for human-robot interaction - Tan, Dilys Hui Ern (Nanyang Technological University, 2020)
In recent years, soft robotics have been in the limelight. Soft robotics refer to the branch of robotics where the mechanical properties of compliant materials are exploited to achieve better performances, including a safer human-robot interaction. Many actuation methods for soft robots have been researched over the past decade and this area of research continues to garner interest. However, most actuation methods are confined to the use of pneumatic systems, mechanical means, or electro-mechanical means. In this report, a novel method to investigate the design of a lightweight single degree-of-freedom hydraulically actuated system with variable mechanical impedance will be introduced, in attempt to establish a safe yet high performing actuation system. Calculation and equations, along with some underlying assumption used to govern the model will be clearly stated. The design process of the proposed system, which involves the use of MATLAB, a script-based modelling software, will be elaborated in further details. The implications of various design parameters will be discussed using the simulation results before final design parameters were selected. Eventually the highlight of the project was to use simulation results to determine the feasibility of designing an actuation system which has hydraulic power transmission while ensuring both safety and good performance characteristics.